EFEK MODERASI DARI KOMISARIS INDEPENDEN PADA HUBUNGAN ANTARA KEPEMILIKAN MANAJERIAL DENGAN KEBIJAKAN DIVIDEN DAN KEBIJAKAN UTANG - Agus Widodo (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
The research was conducted to examine the moderating effects ofboard independent directors on the relationship between managerialownership on dividend policy and debt. The purpose of this study to determinehow much influence managerial ownership on dividend policy and debt aswell as the moderating effects of independent directors on the relationshipbetween managerial ownership on dividend policy and debt.The research wasconducted by quantitative methods using secondary data. Secondary data werefrom Indonesia Capital Market Directory (ICMD) and annual reports listedcompanies on the Indonesia Stock Exchange (IDX). The research populationis a company listed on the Stock Exchange, then the samples were taken bypurposive sampling with the criteria listed companies from 2007 to 2011 andhave the data required in this study. The analysis used the multiple regressionanalysis to see the effect of independent variables on the dependent variableeither jointly or individually. Before being tested by multiple linear regressionfirst tested the classical assumptions.The results showed that the significant negative effect of managerialownership on dividend policy, managerial ownership has no effect on debtpolicy. Independent directors are moderate the relationship betweenmanagerial ownership to dividend policy, but did not moderate therelationship between ownership and debt managerial. Control variables affectthe profitability of dividend policy, size does not affect the dividend policy.While variables affect the profitability and size of debt policy.